2010
DOI: 10.1007/s00441-010-1004-6
|View full text |Cite
|
Sign up to set email alerts
|

A serum fucose-binding lectin (DlFBL) from adult Dicentrarchus labrax is expressed in larva and juvenile tissues and contained in eggs

Abstract: The purification, cloning, sequencing, molecular properties and expression of a fucose-binding lectin from the serum of Dicentrarchus labrax (DlFBL) have been previously reported. We now describe the distribution and expression of DlFBL during fish ontogeny. Immunohistochemistry and in situ hybridization assays were carried out at various developmental stages (from 10 days post-hatching larvae to juveniles). Another fucose-binding lectin, similar to DlFBL in biochemical, immunochemical and agglutinating proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In subsequent studies (Cammarata et al 2007; Salerno et al 2009; Cammarata et al 2012) we established that DlFBL and SauFBL, a lectin from the gilt head sea bream ( Sparus aurata ) of similar binding properties, were both members of the F-type lectin family,and are also present in eggs (Parisi et al 2010). During affinity chromatography of D. labrax serum on L-fucose-agarose a protein peak with hemagglutinating activity that was susceptible to inhibition by L-rhamnose and D-galactose but not by L-fucose was identified, suggesting that this was a serum lectin distinct from DlFBL.…”
Section: Discussionmentioning
confidence: 96%
“…In subsequent studies (Cammarata et al 2007; Salerno et al 2009; Cammarata et al 2012) we established that DlFBL and SauFBL, a lectin from the gilt head sea bream ( Sparus aurata ) of similar binding properties, were both members of the F-type lectin family,and are also present in eggs (Parisi et al 2010). During affinity chromatography of D. labrax serum on L-fucose-agarose a protein peak with hemagglutinating activity that was susceptible to inhibition by L-rhamnose and D-galactose but not by L-fucose was identified, suggesting that this was a serum lectin distinct from DlFBL.…”
Section: Discussionmentioning
confidence: 96%
“…The molecular property of DlFBL showed two tandem carbohydrate-recognition domains displaying F-type sequence motif. In situ hybridization showed that DlFBL distributed in hepatocytes and intestinal cells, as well as in embryonic yolk residues during fish ontogeny12. The function of DlFBL in Dicentrarchus labrax has been linked to enhancing the phagocytosis of microorganisms by macrophages11.…”
mentioning
confidence: 99%
“…20,23,30,31 They are expressed in larval and juvenile tissues and are also stored in eggs. 33 The scarcity of bacteria possessing FTL CRDs suggests that it may have been acquired through horizontal transfer from metazoans. 20 The absence of the FTL CRD in higher vertebrates is an evolutionary enigma that coincides with land colonization after cleidoic egg appearance.…”
Section: Fucose-binding Lectinsmentioning
confidence: 99%
“…17,27 For example, based on the identification of a novel CRD sequence motif 20 and a unique structural fold, 28 the FTL family was identified both in prokaryotes and in fluids and tissues of invertebrates and vertebrates. [29][30][31][32][33][34] …”
Section: Fish Lectinsmentioning
confidence: 99%